Prediction and prevention of small‐for‐gestational‐age neonates: evidence from SPREE and ASPRE. (5th June 2018) - Tan, M. Y.; Poon, L. C.; Rolnik, D. L.; Syngelaki, A.; de Paco Matallana, C.; Akolekar, R.; Cicero, S.; Janga, D.; Singh, M.; Molina, F. S.; Persico, N.; Jani, J. C.; et al.
ABSTRACT: Objectives: To examine the effect of first‐trimester screening for pre‐eclampsia (PE) on the prediction of delivering a small‐for‐gestational‐age (SGA) neonate and the effect of prophylactic use of aspirin on the prevention of SGA. Methods: The data for this study were derived from two multicenter studies. In SPREE, we investigated the performance of screening for PE by a combination of maternal characteristics and biomarkers at 11–13 weeks' gestation. In ASPRE, women with a singleton pregnancy identified by combined screening as being at high risk for preterm PE (> 1 in 100) participated in a trial of aspirin (150 mg/day from 11–14 until 36 weeks' gestation) compared to placebo. In this study, we used the data from the ASPRE trial to estimate the effect of aspirin on the incidence of SGA with birth weight < 10 th, < 5 th and < 3 rd percentile for gestational age. We also used the data from SPREE to estimate the proportion of SGA in the pregnancies with a risk for preterm PE of > 1 in 100. Results: In SPREE, screening for preterm PE by a combination of maternal factors, mean arterial pressure, uterine artery pulsatility index and serum placental growth factor identified a high‐risk group that contained about 46% of SGA neonates < 10 th percentile born at < 37 weeks' gestation (preterm) and 56% of those born at < 32 weeks (early); the overall screen‐positive rate was 12.2% (2014 of 16 451 pregnancies). In the ASPRE trial, use of aspirin reduced the overall incidence of SGA < 10 th percentile by about 40% in babies born at < 37 weeks' gestation and by about 70% in babies born at < 32 weeks; in babies born at ≥ 37 weeks, aspirin did not have a significant effect on incidence of SGA. The aspirin‐related decrease in incidence of SGA was mainly due to its incidence decreasing in pregnancies with PE, for which the decrease was about 70% in babies born at < 37 weeks' gestation and about 90% in babies born at < 32 weeks. On the basis of these results, it was estimated that first‐trimester screening for preterm PE and use of aspirin in the high‐risk group would potentially reduce the incidence of preterm and early SGA by about 20% and 40%, respectively. Conclusion: First‐trimester screening for PE by the combined test identifies a high proportion of cases of preterm SGA that can be prevented by the prophylactic use of aspirin. © 2018 Crown copyright. Ultrasound in Obstetrics & Gynecology © 2018 ISUOG. Abstract : Clickhere to see the Video Abstract of this article.